The Efficacy and Safety of Carbon Ion Radiotherapy for Meningiomas: A Systematic Review and Meta-Analysis - Li, Jie-yun; Li, Jing-wen; Jin, Yuan-chang; Li, Mei-xuan; Guo, Li-ping; Bing, Zhi-tong; Zhang, Qiu-ning; Bai, Fei; Wang, Xiao-hu; Li, Xiu-xia; Yang, Ke-hu (Frontiers in Oncology, 2021)
Objective: The purpose of this systematic review and meta-analysis is to evaluate the efficacy and safety of carbon ion radiotherapy (CI-RT) in improving meningioma by comparing photon and protons radiotherapy. Methods: A comprehensive search for relevant studies published until March 17, 2021, was conducted in PubMed, the Cochrane Library, Chinese Biomedical Literature Database and Embase. Statistical analyses were performed with R 4.0.3. Results: We identified 396 studies, of which 18 studies involving 985 participants were included. Except for one low quality study，the quality of the included studies was found to be either moderate or high quality. The analyses conducted according random effects model indicated that the 1-year overall survival rate (OS) of benign and non-benign meningiomas after the CI-RT treatment was 99% (95%CL=.91-1.00, I2=0%). The overall average 5-year OS for meningiomas was 72% (95%CL=0.52-0.86, I2=35%), not as effective as proton radiotherapy (PR-RT) 85% (95%CL=.72-.93, I2=73, Q=4.17, df=2, p=.12). Additionally, 5-year OS of atypical meningiomas (81%) was found to be significantly higher than anaplastic meningiomas (52%). The 10-year OS after CI-RT of patients with mixed grade meningioma was 91% (95%CL=.75-.97, I2=73%). The 15-year OS after CI-RT 87% (95%CL=.11-1.00) or PR-RT 87% (95%CL=.23-.99, I2=79%) were the same (Q=0, df=1, p=.99). After undergoing CI-RT for 3-years and 5-year, the LC for benign meningioma was 100% and 88%, respectively, while the 2-year LC of non-benign meningiomas (atypical/anaplastic) was 33%. Headache, sensory impairment, cognitive impairment, and hearing impairment were found to be the most common adverse reactions, with individual incidences of 19.4%, 23.7%, 9.1% and 9.1%, respectively. Conclusion: CI-RT is a rapidly developing technique that has been proven to be an effective treatment against meningioma. The efficacy and safety of CI-RT for meningiomas were similar to those of PR-RT, better than photon radiotherapy (PH-RT). However, there is a need for more prospective trials in the future that can help provide more supportive evidence.